2023
DOI: 10.3390/hydrology10030056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Optimum Limited Irrigation and Integrated Nutrient Management Strategies for Wheat Growth, Yield and Quality

Abstract: Agricultural productivity is significantly influenced by the restricted availability of irrigation water and poor soil health. To assess the influence of different potential soil moisture deficit (PSMD) regimes and integrated nutrient levels on the growth, yield, and quality of wheat, an experiment was carried out at the research area of the University of Agriculture, Faisalabad. The experiment includes three levels of PSMD (I1: 25 mm PSMD, I2: 50 mm PSMD, and I3: 75 mm PSMD) and four integrated nutrition leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Drought conditions are prevailing around the globe very rapidly due to climate-induced variations in precipitation and competing land interests for economic growth [ 54 ], putting global food security at risk [ 31 ]. It is widely recognized that water shortage significantly influences various metabolic and physiological disorders in plants [ 55 , 56 ]. We observed that both cultivars of flax showed a decline in shoot length, shoot fresh and dry weight in response to drought treatments ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Drought conditions are prevailing around the globe very rapidly due to climate-induced variations in precipitation and competing land interests for economic growth [ 54 ], putting global food security at risk [ 31 ]. It is widely recognized that water shortage significantly influences various metabolic and physiological disorders in plants [ 55 , 56 ]. We observed that both cultivars of flax showed a decline in shoot length, shoot fresh and dry weight in response to drought treatments ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pulses are environmentally friendly products due to their reduced use of inputs such as irrigation and agrochemicals, i.e., pesticides and fertilizers. Legume-based cropping systems enhance the sustainability of production systems by increasing soil biodiversity, soil health and quality, crop productivity, soil restoration, and food security [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The clay loam soil nature of the experimental site might have contributed to hypoxia conditions and hindered vegetative growth. Abubaker et al (2014), You et al (2022) and Zulfiqar et al (2023) support positive irrigation effects on plant height within growth-conducive limits. Earlier research also highlights the link between irrigation and tiller numbers, crucial for final grain yield.…”
Section: Effect Of Irrigation Schedules On Plant Growth Parametersmentioning
confidence: 95%